THE INCONSISTENCY OF ICSID AWARDS OVER ARGENTINA CASES - Aiyub Kadir, M. Ya'kub; Farsia, Lena (Hasanuddin University, 2020)
This paper discusses the inconsistency of International Centre for Settlement of Investment Disputes (ICSID) awards over an emergency situation in Argentina in 2001. Utilising a doctrinal methodology under Third World Approach to International Law (TWAIL) paradigm, this paper explores the argument set out in Argentina case in the first trial and its appeals, then makes an effort to find out the better and systematic argument for Argentina. Therefore, this paper contributes to factually understanding the different argument from two perspectives in ICSID proceedings which has been contested and herewith proposed a better formulated argument for the future of ICSID awards making by placing economic development in Third World States as a basis of argument. Hence this argument can be used for the similar cases in the ICSID in future.